Study on the mechanism of carbide precipitation by surface quenching treatment on GCr15 bearing rings based on the phase-field method - Liu, Qian; Jiang, Jiaxuan; Chen, Ming; Deng, Xiaohu; Wang, Jiangang; Ju, Dongying (Frontiers in Materials, 2022)
In this paper, the thermodynamics database describing Gibbs free energy of FCC phase and M23C6 phase based on Fe-Cr-C ternary alloy was coupled into phase field simulation, and the phase field model was developed on the mesoscopic scale which simulates precipitation, growth and coarsening of M23C6 carbides in FCC austenitic matrix by considering the elastic energy. As the boundary condition of imported phase field calculation, the heat treatment COSMAP software was applied to obtain the macro numerical simulation results of quenching. The phase composition, element distribution, and the evolution including the nucleation, growth and coarsening was simulated by phase field method for the M23C6 carbides in quenching process of GCr15 bearing ring. By means of comparison between the calculation results of phase field simulation and the morphology, quantity and distribution of carbides observed by SEM experiment, this paper present the mechanism on precipitation of micro M23C6 carbides influenced by quenching process parameters, and the experiment verifies the feasibility and accuracy of phase field simulation.